2020
DOI: 10.1111/petr.13800
|View full text |Cite
|
Sign up to set email alerts
|

Time to second kidney transplantation in young adults after failed pediatric kidney transplant

Abstract: Background: Under the current kidney allocation system, pediatric candidates listed prior to age 18 receive priority for high-quality deceased donor organs. This has resulted in a decline in living donor transplantation in pediatrics, despite superior outcomes of living donor transplantation. Due to a young age at transplantation, most pediatric kidney transplant recipients require re-transplantation. The effects of a previously failed deceased donor vs a previously failed living donor on re-transplant candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“… 10 , 11 Studies also show greater sensitization and lower rates of transplant in patients who undergo transplant with a DD kidney first compared with an LD kidney first, which further supports an LD-first sequence. 10 , 11 Delays may be unavoidable (eg, precipitous graft loss, delay in LD workup or finding a new LD). For recipients who have developed HLA antibodies to their LD transplant, entering a paired exchange registry or desensitization are options.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“… 10 , 11 Studies also show greater sensitization and lower rates of transplant in patients who undergo transplant with a DD kidney first compared with an LD kidney first, which further supports an LD-first sequence. 10 , 11 Delays may be unavoidable (eg, precipitous graft loss, delay in LD workup or finding a new LD). For recipients who have developed HLA antibodies to their LD transplant, entering a paired exchange registry or desensitization are options.…”
Section: Discussionmentioning
confidence: 72%
“… 12 Individuals with reduced access to transplant, live donation, or preemptive listing will have worse outcomes in both sequences. 11 We did not reduce transplant rates for a second transplant due to sensitization. Although sensitization will affect subsequent transplant rates, the current Kidney Allocation System has demonstrated an ability to transplant in those who are sensitized (≤98%) at a rate that is not very different from those less sensitized.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher sensitization after brief exposure to a thrombosed living donor kidney was associated with a 37% reduction in the chance of a second transplant [19]. In young adults, the recipient's sensitization was higher after a failed first deceased donor when compared with a living donor, with consequent delay to a second transplant [20]. Early graft loss in adult kidney recipients was associated with high mortality rates in the first few months after transplantation, low re-listing rates, and increased risk of a subsequent early graft loss [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recipient characteristics associated with increased risk of graft failure in 10-15 kg pediatric kidneys donor transplants were a recipient time in dialysis, morbid obesity (BMI >40), diabetes mellitus, and age over 60 years. 13 (12)(13)(14) 14 (12)(13)(14)(15) 17 (16)(17) 17 (16)(17)(18) 19 (19)(20) 20 (19)(20) 62 (45-74) DCD (%) In a sub-analysis, single kidney donors were stratified in 10, 11, 12, 13, and 14 kg weight to compare graft survival with the >20 kg single group. The Kaplan-Meier curve demonstrated that donors with weight <12 kg had an inferior survival.…”
Section: Transplant Complicationsmentioning
confidence: 99%